2013
DOI: 10.1371/journal.pone.0062837
|View full text |Cite
|
Sign up to set email alerts
|

CKD273, a New Proteomics Classifier Assessing CKD and Its Prognosis

Abstract: National Kidney Foundation CKD staging has allowed uniformity in studies on CKD. However, early diagnosis and predicting progression to end stage renal disease are yet to be improved. Seventy six patients with different levels of CKD, including outpatients and dialysed patients were studied for transcriptome, metabolome and proteome description. High resolution urinary proteome analysis was blindly performed in the 53 non-anuric out of the 76 CKD patients. In addition to routine clinical parameters, CKD273, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 27 publications
4
120
0
Order By: Relevance
“…The process appears to be regulated by transforming growth factor-β1 [75] and emerging evidence suggests it exerts a renoprotective role [76] , which is possibly, at least in part, related to its capability to degrade insoluble collagen I [77] . In support of this notion, a urine peptidome study in CKD patients has demonstrated an inverse correlation between the amount of collagen I and III breakdown products and CKD progression [78,79] .…”
Section: Autophagymentioning
confidence: 89%
“…The process appears to be regulated by transforming growth factor-β1 [75] and emerging evidence suggests it exerts a renoprotective role [76] , which is possibly, at least in part, related to its capability to degrade insoluble collagen I [77] . In support of this notion, a urine peptidome study in CKD patients has demonstrated an inverse correlation between the amount of collagen I and III breakdown products and CKD progression [78,79] .…”
Section: Autophagymentioning
confidence: 89%
“…This most likely confers the previously observed predictive abilities of the classifier. 19,20,28 Finally, the size of the cohort allowed the identification of urinary peptides specifically associated with mild-moderate or advanced stage CKD as well. To our knowledge, this is the first time that potential biomarkers were analyzed with respect to their association with different stages of CKD and hence may allow further stratification of patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Although initially designed for the detection of CKD, employment of the classifier also allowed prediction of progression of CKD in patients with CKD derived from different aetiologies 28,29 , including patients with DN 30,31 .…”
Section: Introductionmentioning
confidence: 99%